Clinical challenges in the dosing and titration of cariprazine - Miljević, Čedo D.; Vuković, Petar G.; Munjiza-Jovanović, Ana (Frontiers in Psychiatry, 2024)
The introduction of a new psychopharmaceutical medication instead of the previous one always poses a certain challenge. In the case of antipsychotics (AP), these problems are considerably more complicated and are mainly caused by the question of dose equivalents, but also by the pharmacokinetic properties of the drug. In the case of partial dopamine D2 agonists, an additional issue is the possibility of deterioration when switching from the previous D2 antagonists to these drugs. Cross-titration is therefore generally recommended. Finally, due to the capsule form, it is not possible to increase the dose of cariprazine by less than 1.5 mg during titration. In this paper, we have presented our proposal to replace the most commonly used second-generation APs with the third-generation AP cariprazine. We have taken into account the dose equivalents, the pharmacological forms of the drugs and their pharmacokinetic and pharmacodynamic properties.